solve x^3+2x^2+x=0

factorise x3+2x2+x=0 => x(x2+2x+1)=0 => x(x+1)(x+1)=0 => x(x+1)2=0 => This leads to x=0 and (x+1)2=0 so x=0 and x+1=0 => Giving us the answer x=0,-1

Answered by Robbie R. Maths tutor

4337 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

how to turn a fraction in the form of (x + a)/(x + b)^2 into partial fractions?


what is d(2x^3)/dx?


y = (x^2)sin(3x). Find dy/dx


Solve D/dx (ln ( 1/cos(x) + tan (x) )


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences